A multicriteria prioritization model to support public safety planning - Gurgel,André Morais (2013)
Setting out to solve operational problems is a frequent part of decision making on public safety. However, the pillars of tactics and strategy are normally disregarded. Thus, this paper focuses on a strategic issue, namely that of a city prioritizing areasin which there is a degree of occurrences for criminality to increase. A multiple criteria approach is taken. The reason for this is that such a situation is normally analyzed from the perspective of the degree of police occurrences. The proposed model is based on a SMARTS multicriteria method and was applied in a Brazilian City. It combines a multicriteria method and a Monte Carlo Simulation to support an analysis of robustness. As a result, we highlight some differences between the model developed and police occurrences model. It might support differentiated policies for zones, by indicating where there should be strong actions, infrastructure investments, monitoring procedures and others public safety policies.